2023
DOI: 10.3390/ijms24108690
|View full text |Cite
|
Sign up to set email alerts
|

Omics Analysis Unveils the Pathway Involved in the Anthocyanin Biosynthesis in Tomato Seedling and Fruits

Abstract: The purple tomato variety ‘Indigo Rose’ (InR) is favored due to its bright appearance, abundant anthocyanins and outstanding antioxidant capacity. SlHY5 is associated with anthocyanin biosynthesis in ‘Indigo Rose’ plants. However, residual anthocyanins still present in Slhy5 seedlings and fruit peel indicated there was an anthocyanin induction pathway that is independent of HY5 in plants. The molecular mechanism of anthocyanins formation in ‘Indigo Rose’ and Slhy5 mutants is unclear. In this study, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…In addition, other transcription factors that may be involved in the regulation of anthocyanin synthesis were also identified, e.g., 18 bZIPs , 20 NACs , and 9 MADSs were differentially expressed in the two mung bean varieties, respectively. Notably, many studies have identified regulatory genes beyond the MYB-bHLH-WD40 ternary complex e.g., peach PpNAC1 ( Zhou et al., 2015 ), tomato SlHY5 ( He et al., 2023 ), and sweet potato IbMADS10 ( Dong et al., 2016 ) are all involved in the regulation of anthocyanin biosynthesis. These data suggest that plant anthocyanin biosynthesis is controlled by a complex and sophisticated regulatory network.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other transcription factors that may be involved in the regulation of anthocyanin synthesis were also identified, e.g., 18 bZIPs , 20 NACs , and 9 MADSs were differentially expressed in the two mung bean varieties, respectively. Notably, many studies have identified regulatory genes beyond the MYB-bHLH-WD40 ternary complex e.g., peach PpNAC1 ( Zhou et al., 2015 ), tomato SlHY5 ( He et al., 2023 ), and sweet potato IbMADS10 ( Dong et al., 2016 ) are all involved in the regulation of anthocyanin biosynthesis. These data suggest that plant anthocyanin biosynthesis is controlled by a complex and sophisticated regulatory network.…”
Section: Discussionmentioning
confidence: 99%
“…However, consistent with the results reported in other plant species, Slhy5 mutants still accumulate residual anthocyanins in the fruit peel under high light [ 180 ]. Transcriptome analysis of several tissues of the knockout Slhy5 mutants in the ‘Indigo Rose’ background allowed the identification of candidate TFs belonging to different families, such as HD-bZIP, WRKY, NAC, and PIF, which probably play roles in regulating anthocyanin synthesis in tomatoes in an HY5-independent manner, under high-light [ 180 , 240 ]. Notably, through yeast two-hybrid (Y2H) assays, He et al [ 240 ] showed that SlBBX24, SlWRKY44, and, unexpectedly, two PIF TFs, SlPIF1 and SlPIF3, physically interacted with some of the TFs contributing to the formation of the MBW complex.…”
Section: Tomatomentioning
confidence: 99%
“…Transcriptome analysis of several tissues of the knockout Slhy5 mutants in the ‘Indigo Rose’ background allowed the identification of candidate TFs belonging to different families, such as HD-bZIP, WRKY, NAC, and PIF, which probably play roles in regulating anthocyanin synthesis in tomatoes in an HY5-independent manner, under high-light [ 180 , 240 ]. Notably, through yeast two-hybrid (Y2H) assays, He et al [ 240 ] showed that SlBBX24, SlWRKY44, and, unexpectedly, two PIF TFs, SlPIF1 and SlPIF3, physically interacted with some of the TFs contributing to the formation of the MBW complex. Overall, their findings led the authors to speculate on the possible involvement of SlPIF1 , SlPIF3 , SlBBX24 , and SlWRKY44 in anthocyanin biosynthesis in a SlHY5-independent or dependent manner.…”
Section: Tomatomentioning
confidence: 99%
“…Por su parte, Cesa et al (2017), realizaron procesos combinando de tratamiento sobre extractos de blueberry tales como homogenizado con Ultramax y pasteurizado a diferentes tiempos y temperaturas, como resultado el mayor contenido de antocianinas lo obtuvieron las muestras pasteurizadas a 70 °C por 15 s con 2 740±53 mg DGEB (delphinidin-3-O-galactoside equivalente) 100g -1 . La variación en el contenido de polifenoles y antocianinas, estaría relacionado con factores agronómicos como las prácticas de cultivo, pH del suelo, microbioma, fertilizantes (Zhou et al, 2022), riego y factores climáticos, incluso factores de estrés, la fotoinhibición, disminución de temperatura, la deficiencia de nutrientes, heridas o el ataque de patógenos, incrementan la acumulación de antocianinas en las plantas (Routray y Orsat, 2011), también durante el desarrollo de las frutas ocurren procesos metabólicos en el incremento de producción de antocianinas (Pott et al, 2020), por ejemplo, en tomate, el gen SlHY5 es responsable de la producción de antocianinas (He et al, 2023).…”
Section: Muestrasunclassified